A review on mechanism, applications and influencing factors of carbon quantum dots based photocatalysis. Issue 24 (15th December 2022) - Gao, Wensu; Zhang, Shurong; Wang, Guiqiao; Cui, Jinzhi; Lu, Yaxin; Rong, Xing; Gao, Canzhu
Abstract: CQDs (carbon quantum dots) have attracted a lot of attention in the field of photocatalysis due to its absorption of visible light, up-conversion luminescence, rich free groups on the surface and low cost. CQDs doped semiconductor can improve the photocatalytic reaction rate by the following three points: (1) adjust the band structure of photocatalyst; (2) facilitate the absorption of more visible light; (3) facilitate electron transfer and inhibits electron-hole recombination. In this review, the mechanism (photosensitizer, electron acceptor, up-conversion luminescence, etc.) and applications (photocatalytic degradation of organic pollutants, reduction of heavy metals, etc.) of CQDs in the field of photocatalysis are briefly introduced. Finally, the factors affecting the photocatalytic activity were summarized in order to adjust the reaction conditions and show high catalytic activity. It is hoped that this review can provide insights and inspiration for the development of CQDs in the field of photocatalysis.